Tinjauan Akuntansi Syariah terhadap Akuntansi Pembiayaan Murabahah pada Bank Syariah Indonesia Cabang Banda Aceh - Mardiaton, Mardiaton; Mahdani, Rimal; Elisyah, Nur; Aryani, Irne; Murni, Murni (Jurnal Akuntansi dan Keuangan, 2025)
The objective of this study is to analyze and determine the murÄbahah financing system carried out at Bank Syariah Indonesia (BSI) of Banda Aceh in accordance with Islamic accounting reviews. This is a descriptive research with primary and secondary data directly obtained from research site, and variety of literatures respectively. The results of the study which was carried out at BSI, indicate that accounting for murÄbahah transactions has not been fully utilized in accordance with (PSAK) (Statement of Financial Accounting Standards) PSAK Number: 102. Similarly, some transactions cannot also be recorded because the bank expects the customer to purchase goods by providing a certain amount of funds. The recognition of the murÄbahah profit still uses the annuity method and the inventory of its assets has never been presented in the statement of financial position due to its unavailability by the bank.